Transforming lives: Taoheed Ajala Kehinde & Oladoja Samuel's journey with farmers outreach - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2025)
In this video, Taoheed Ajala Kehinde & Oladoja Samuel displayed the ripple effect of knowledge and how Radio IITA training helped both of them overcome the challenge of low yield in cowpea farming.